The Differences in Serum Complements and Anti-dsDNA Levels between Renal and Non-renal Manifestations in Systemic Lupus Erythematosus - Bagus Putu Putra Suryana; Lya Rosita; Nursamsu Djais; Dian Hasanah (Indonesian Rheumatology Association, 2019)
Background. Systemic lupus erythematosus (SLE) has diverse clinical manifestations, including renal and non-renal. Renal manifestation is related to significant morbidity and mortality. SLE is also characterized by serological aberrations, including levels of complement C3, C4 and anti-dsDNA, but the association of them with clinical manifestations including renal and non-renal is unclear. This study investigated the associations of C3, C4 and anti-dsDNA levels with renal and non-renal manifestations in SLE patients. Method. A cross-sectional study was conducted in the Polyclinic of Rheumatology, Dr. Saiful Anwar Hospital Malang. A number of 43 subjects fulfilled the 1997 American College of Rheumatology criteria participated in this study, that consisted of 11 patients with renal manifestation and 32 patients with non-renal manifestations. Serum C3 and C4 levels were measured using immunoturbidimetry, and serum anti-dsDNA levels were measured using enzyme-linked immunosorbent assays (ELISA). The independent T-test was used to compare C3 levels and the Mann-Whitney U test was used to compare C4 and anti-dsDNA levels between groups. Result. SLE with renal manifestation had significant lower levels of serum C3 compare to non-renal manifestations (mean ± SD: 71.27 ± 32.65 mg/dL and 94.47 ± 26.29 mg/dL respectively, p=0.022). SLE with renal manifestation also had significantly lower levels of serum C4 compare to non-renal manifestations (mean ± SD: 14.55 ± 8.20 mg/dL and 25.50 ± 11.05 mg/dL respectively, p=0.002). Conversely, SLE with renal manifestation had significantly higher levels of serum anti-dsDNA compare to non-renal manifestations (mean ± SD: 249.27 ± 240.34 IU/mL and 109.91 ± 166.11 IU/mL respectively, p=0.014). Conclusion. SLE patients with renal manifestation have significantly lower levels of serum C3 and C4 and a higher level of serum anti-dsDNA than SLE patients with non-renal manifestations.